2020
DOI: 10.1097/jcn.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Heart Failure Symptoms at Hospital Discharge Predicts 30-Day Clinical Events

Abstract: Background: The relationship between heart failure (HF) symptoms at hospital discharge and 30-day clinical events is unknown. Variability in HF symptom assessment may affect ability to predict readmission risk. Objective: The aim of this study was to describe HF symptom profiles and burden at hospital discharge. A secondary aim was to examine the relationship between symptom burden at discharge and 30-day clinical events. Methods: An exploratory descriptive design was used. Patients with HF (n = 186) were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Challenges such as symptom clusters, inadequate symptom-related knowledge, poor assessment skills, and lack of trust in health professionals' expertise and support hinder the management of these complex symptoms [16]. According to the middle-range theory of unpleasant symptoms, certain physiological factors, including comorbidities [17], and psychological factors are associated with symptom burden and management [18]. A higher burden of symptoms impairs daily living activities, QoL, and self-management behaviors in HF patients [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges such as symptom clusters, inadequate symptom-related knowledge, poor assessment skills, and lack of trust in health professionals' expertise and support hinder the management of these complex symptoms [16]. According to the middle-range theory of unpleasant symptoms, certain physiological factors, including comorbidities [17], and psychological factors are associated with symptom burden and management [18]. A higher burden of symptoms impairs daily living activities, QoL, and self-management behaviors in HF patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…The direct effect of coexisting comorbid conditions in HF on worse clinical outcomes, higher symptom burden, poor medication adherence [1], and its relationship with reduced self-management ability [4,16] shows the vital need for symptom management and medication adherence in HF patients with comorbidities [4,8,12,17]. The significant effect of non-invasive telemonitoring on HF care-related costs, the incidence of acute non-fatal HF events [19], and the impact of telephone-based self-management programs on improving health awareness and symptom recognition is clear [20].…”
Section: Introductionmentioning
confidence: 99%
“…5 A hallmark of JCN has been the outstanding research that advances heart failure nursing including landmark heart failure self-care theory, [6][7][8] innovative interventions, [9][10][11] and advances in heart failure symptom science. [12][13][14][15] These articles, along with a collection of heart failure caregiver research, can be found in the special collections section of the JCN website. Cardiovascular nursing research focused on advancing heart failure care is more important than ever.…”
mentioning
confidence: 99%